EFEK LOKASI INJEKTOR TERHADAP INDEKS PENCAMPURAN AMMONIA UNTUK SCR DENGAN MIXER DINAMIK - Syaiful, Syaiful; Andriani, Iseu (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2014)
Diesel engines many are used as transportation mode in the land and sea compared with gasoline engines due to their high efficiency and durability. However, diesel engine releases much more NOx and soot emissions than that of gasoline engine. NOx is formed from a reaction of Nitrogen and Oxygen at high temperature. If these emissions are breathed into human body resulting respiratory disorders such as emphysema and bronchitis as well as lungs tissue damage. Therefore, NOx emissions controll is required to reduce them reaching under a threshold level. An effective method for controlling NOx emissions produced by the diesel engines is by injecting ammonia obtained from urea into selective catalytic reduction (SCR method) system. Ammonia by means of catalyst reacts with NOx forming Nitrogen (N2) and Water (H2O). Therefore, a chance of each ammonia particle to react with each NOx particle is required to consider. A reaction quality between ammmonia and NOx particles can be increased by improving a mixing index. One of the methods to increase the mixing index is by using a dynamic mixer.There are several factors which influence the increase of mixing index. One of these factors is a location of ammonia injector. Since this work is focused on investigating the effect of ammonia injector location on the mixing index of ammonia to diesel engine exhaust gases which content of NOx emissions